2005
DOI: 10.1158/1055-9965.epi-05-0143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in XRCC1, APE1, ADPRT, XRCC2, and XRCC3 and Risk of Chronic Benzene Poisoning in a Chinese Occupational Population

Abstract: DNA damage induced by benzene is an important mechanism of its genotoxicity that leads to chronic benzene poisoning (CBP). Therefore, genetic variation in DNA repair genes may contribute to susceptibility to CBP in the exposed population. Because benzene-induced DNA damage includes single-and double-strand breaks, we hypothesized that single-nucleotide polymorphisms in X-ray repair crosscomplementing group 1 (XRCC1), apurinic/apyrimidinic endonuclease (APE1), ADP ribosyltransferase (ADPRT), X-ray repair cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 47 publications
2
25
1
2
Order By: Relevance
“…In this study, we found that the frequency of the T allele was twofold higher in gastric cancer patients. Also, the G allele of the APE gene family was observed more frequently in patients with common digestive system cancer types [24,28]. In the present study, the frequency of the G allele was 0.78 and therefore high.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In this study, we found that the frequency of the T allele was twofold higher in gastric cancer patients. Also, the G allele of the APE gene family was observed more frequently in patients with common digestive system cancer types [24,28]. In the present study, the frequency of the G allele was 0.78 and therefore high.…”
Section: Discussionsupporting
confidence: 49%
“…Linking variation in polymorphic sites of the XRCC2 and XRCC3 has been conducted for various cancer types [22][23][24]. It was found that the XRCC3 Th r241Met polymorphism was associated with the risk of breast cancer [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что устойчивый метаболит бензола р-бензо-хинон, формирует р-бензохин-С аддукты, являющиеся субстратом для апуриновой/апиримидиновой эндо-нуклеазы (APE1). После вырезания таких аддуктов в зашивании бреши принимают участие ферменты экци-зионной репарации оснований XRCC1, ДНК-лигаза III, в том числе и XPС (Zhang, et al, 2005).…”
Section: Discussionunclassified
“…Ген ERCC2 (XPD), так же как и XPC, входит в группу NER-генов. Ген XPD ко-дирует геликазу, являющуюся частью транскрипци-онного фактора TFIIH, и, соответственно, изменения, затрагивающие функциональную активность XPD, изменяют способность к восстановлению структу-ры ДНК, что характеризуется повышением числа ДНК-аддуктов у лиц, носителей этого аллеля (Kiyohara et al, 2007 27), что объясняется имеющимися межэтническими различиями в распре-делении аллелей и генотипов по данному локусу между населением Европы и Азии и малочисленностью изу-чаемых выборок.…”
Section: Discussionunclassified